Upaya bersihan jalan napas dengan posisi semi fowler dan teknik batuk efektif pada pasien ISPA di Desa Lempasing - Lina, Mia Nurar; Yulendasari, Rika; Chrisanto, Eka Yudha (JOURNAL of Public Health Concerns, 2025)
Background: Acute respiratory infection (ARI) is an infectious disease that affects the upper and lower respiratory tract and can progress to pneumonia, and is transmitted through the air. Globally, ARI causes millions of deaths each year, and Indonesia recorded the highest prevalence in ASEAN, including 35.9% of cases in Lampung Province in 2020. Increased bronchial secretions in ARI patients create nursing problems in the form of ineffective airway clearance, which can be addressed through pharmacological and non-pharmacological interventions such as the semi-Fowler's position and effective coughing to improve respiratory function. Purpose: To determine the effectiveness of the semi-Fowler's position and effective coughing techniques in improving airway clearance in ARI patients, as non-pharmacological efforts that support respiratory function recovery and reduce secretion accumulation. Method: This activity was conducted in Lempasing Village from May 21–26, 2025, with two patients with acute respiratory infections (ARI) as respondents. Nursing interventions, including the semi-Fowler's position and effective coughing, were implemented for three days and analyzed using a case study approach to evaluate improvements in airway clearance. Data on the amount of sputum collected in sputum pots were collected twice: in the morning (9:00 AM - 4:00 PM) and in the afternoon (4:00 PM - 9:00 PM), with sputum volume used as a measure of airway clearance. Sputum volume data was tabulated to observe changes before (pre-test) and after (post-test) the intervention. Results: The total sputum volume of respondent 1 was 140 cc in the pre-test, 115 cc in the post-test, and 70 cc in the post-test. Meanwhile, the total sputum volume of respondent 2 in the pre-test was 120 cc, in post-test 1 it was 80 cc and in post-test 2 it was 60 cc. Conclusion: Applying the semi-Fowler's position combined with effective coughing techniques twice daily for three days significantly reduced sputum volume in patients with acute respiratory infections (ARI), as reflected in a 50% reduction in secretion production in both respondents, thereby increasing the effectiveness of airway clearance. Suggestion: For nursing practice, the semi-Fowler's position and effective coughing should be routinely integrated at least twice daily in patients with acute respiratory infections to support airway clearance. Keywords: Acute respiratory infections (ARI); Airway clearance; Effective cough; Semi-Fowler's position Pendahuluan: Infeksi saluran pernapasan akut (ISPA) merupakan penyakit menular yang menyerang saluran pernapasan atas maupun bawah dan dapat berkembang menjadi pneumonia, dengan penularan melalui udara. Secara global, ISPA menyebabkan jutaan kematian setiap tahun, dan Indonesia mencatat prevalensi tertinggi di ASEAN, termasuk 35.9% kasus di Provinsi Lampung pada tahun 2020. Peningkatan sekret bronkus pada pasien ISPA menimbulkan masalah keperawatan berupa bersihan jalan napas tidak efektif, yang dapat ditangani melalui intervensi farmakologis dan nonfarmakologis seperti posisi semi-fowler, dan batuk efektif untuk memperbaiki fungsi pernapasan. Tujuan: Mengetahui efektivitas posisi semi-fowler dan teknik batuk efektif dalam meningkatkan bersihan jalan napas pada pasien ISPA, sebagai upaya nonfarmakologis yang mendukung pemulihan fungsi pernapasan dan mengurangi akumulasi sekret. Metode: Kegiatan ini dilaksanakan di Desa Lempasing pada 21–26 Mei 2025 dengan dua pasien ISPA sebagai responden. Intervensi keperawatan berupa posisi semi-fowler dan batuk efektif diterapkan selama tiga hari dan dianalisis menggunakan pendekatan studi kasus untuk mengevaluasi peningkatan bersihan jalan napas. Pengambilan data jumlah sputum yang terkumpul di sputum pot, dilakukan dua kali yaitu periode pagi (09.00 - 16.00) dan sore hari (16.00 - 21.00) dimana volume sputum sebagai data ukur bersihan napas. Data volume sputum ditabulasikan untuk melihat perubahan dari sebelum (pre-test) dan sesudah (post-test) intervensi.. Hasil: Menunjukkan bahwa total volume sputum responden 1 pada pre-test sebanyak 140 cc, pada post-test1 sebanyak 115 cc dan pada post-test2 sebanyak 70 cc. Sedangkan untuk total volume sputum responden 2 pada pre-test sebanyak 120 cc, pada post-test1 sebanyak 80 cc dan pada post-test2 sebanyak 60 cc. Simpulan: Penerapan posisi semi-fowler dipadu teknik batuk efektif dua kali sehari selama tiga hari terbukti secara signifikan menurunkan volume sputum pada pasien ISPA, yang tercermin dari penurunan produksi sekret hingga 50% pada kedua responden, sehingga meningkatkan efektivitas pembersihan jalan napas. Saran: Untuk praktik keperawatan, intervensi posisi semi-fowler dan batuk efektif sebaiknya diintegrasikan secara rutin minimal dua kali sehari pada pasien ISPA guna mendukung bersihan jalan napas.